2006
DOI: 10.1007/s10546-005-9047-z
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Incomplete Surface Energy Balance Closure for CO2 Fluxes from Open-Path CO2/H2O Infrared Gas Analysers

Abstract: Abstract. We present an approach for assessing the impact of systematic biases in measured energy fluxes on CO 2 flux estimates obtained from open-path eddy-covariance systems. In our analysis, we present equations to analyse the propagation of errors through the Webb, Pearman, and Leuning (WPL) algorithm [Quart. J. Roy. Meteorol. Soc. 106, 85-100, 1980] that is widely used to account for density fluctuations on CO 2 flux measurements. Our results suggest that incomplete energy balance closure does not neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 42 publications
0
41
0
1
Order By: Relevance
“…CO2 flux by the eddy covariance technique using an infrared open-path CO2/H2O gas analyzer may include some uncertainties of the Webb correction, cross-sensitivity, energy balance closure, and so on. Liu et al (2006) suggested that incomplete energy balance closure does not necessarily lead to an underestimation of CO2 flux. Our result suggested that the Webb correction may cause an overestimated correction of CO2 and H2O fluxes over a dry asphalt surface where there is no cross-sensitivity between H2O and CO2 gases by an infrared open-path CO2/H2O gas analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…CO2 flux by the eddy covariance technique using an infrared open-path CO2/H2O gas analyzer may include some uncertainties of the Webb correction, cross-sensitivity, energy balance closure, and so on. Liu et al (2006) suggested that incomplete energy balance closure does not necessarily lead to an underestimation of CO2 flux. Our result suggested that the Webb correction may cause an overestimated correction of CO2 and H2O fluxes over a dry asphalt surface where there is no cross-sensitivity between H2O and CO2 gases by an infrared open-path CO2/H2O gas analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…When measuring fluxes of air constituents in volume-related units (in contrast to mass-related ratios such as dry mole fractions) the so called WPL-correction (Webb et al, 1980) has to be applied in order to compensate for density fluctuations and a vertical mass flow. No additional corrections to the original WPLapproach, such as the influence of the lack of energy balance closure (Liu et al, 2006), the effects of window dirtiness (Serrano-Ortiz et al, 2008), or sensor induced density fluctuations (Grelle and Burba, 2007) were applied. All processing steps after the calculation of the covariances were carried out iteratively in some of the software packages because of their partial interdependence.…”
Section: Datasets and Softwarementioning
confidence: 99%
“…The main difference is that the uncertainty estimate is based on differences between fluxes measured on subsequent days if environmental conditions were similar on both days. Because most often environmental conditions are not the same on two subsequent days (Liu et al, 2006), the applicability of this method suffers from a lack of data and the random error is overestimated (Dragoni et al, 2007). The model residual approach (Dragoni et al, 2007;Hollinger and Richardson, 2005;Richardson et al, 2008) calculates CO 2 fluxes with a simple model and compares calculated values with measured values.…”
Section: Introductionmentioning
confidence: 99%